LEGAL KNOWLEDGE AS A DEVELOPMENT FACTOR OF THE MODERN CULTURAL AND POLITICAL-LEGAL ENVIRONMENT - Smal, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Goal: the analysis of the legal knowledge potential as a development factor of the cultural and political-legal environment, means of understanding and acknowledging of the legal reality, as well as the intellectual basis of the lawful conduct. To achieve the above mentioned goal, the papers of both Ukrainian and foreign researchers were examined, specifically the phenomena of the legal knowledge in terms of the analysis of its role in the system of the events and processes, which are affecting the development of the state and law itself. Methods used in the paper: theoretical research used the corresponding methods, namely analytical and generalization of the cultural and systematic approaches. Results: as a result the following conclusions were made: 1) mastery of the day-to-day legal knowledge has a positive effect on the legal consciousness formation as well as on the legal culture and society in general; 2) legal knowledge, its spreading and acknowledgment, are the factors of consolidation within the society, because such knowledge is a basis for the communication with a significant potential for the efficient social institutions. Discussion: the fact that all objects, events and processes, which are involved in the activity of the mankind, have social and interpersonal interpretation of some kind, based on the certain knowledge - is one of the philosophical paradigms of the present days. Therefore the knowledge, in its subjective form, is an important element of the culture of identity, hence legal knowledge – the part of legal culture and consciousness. Legal knowledge is also forming some kind of positive communication in the society. As a result, the importance of the law education for the citizens is crucial, consequences of its neglect speak for themselves.